Developing a model of soft-skill teaching for civil engineering students - Azwar Inra; Sukamto Sukamto; Z. Mawardi Effendi (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2016)
An observation shows that civil engineering students’ soft skill is still low. It is characterized by their poor sociability and low positive attitude toward dealing with problems and challenges of life. For students to have various aspects of soft skill, a study was conducted to develop a model of soft-skill teaching that would meet the criteria of validity, effectiveness, and practicality. The research and development referred to Richey Klein approach, which is: (1) developing a model; and (b) validating a model. The validation process was conducted in two phases, namely internal validation and external validation. The internal validation of the model and its components was conducted by experts in educational technology, vocational education, and evaluation. On the other hand, the external validation was conducted in the form of small groups and of large groups which involved 41 students and a member of the Department of Civil Engineering Board. The data analysis was performed in two phases: the developmental phase and the testing phase. The analysis in the development phase was conducted by means of the qualitative approach, while the analysis in the testing stage was conducted by means of the quantitative approach; the two phases should be undergone to analyze the model validation and the trial results. These phases would also be undertaken by the experts. The results of the study show that the model of soft-skill teaching developed for the students of the department of civil engineering had been able to meet the criteria of validity, effectiveness, and practicality.